The Patterns of Drug and Alcohol Use and Associated Problems over 30 Years in 397 Men - Schuckit, Marc A. (2013)
BACKGROUND: Alcohol- and drug-use disorders (AUDs and SUDs) and their combination are relatively common, and often occur together. However, the relationships of potential early life correlates of alcohol and drug disorders to the combined diagnoses have rarely been evaluated in long-term prospective studies or in populations at high risk for one of these diagnoses but not the other. METHODS: Data were analyzed from 397males (half with an alcohol-dependent father) who had no AUDs or SUDs at age 20 and who were followed ~every five years for three decades. Early life correlates and the course of AUDs, SUDs, and combined disorders were evaluated for four groups of subjects based on subsequent alcohol and/or drug diagnoses. RESULTS: While the overall rates of the development of AUDs and SUDs were 41% and 21%, respectively, the rates of the second substance-related diagnosis were almost two-fold higher for individuals who had the first condition. Among potential risk factors, scores for externalizing traits were elevated for men with AUDs, SUDs, and their combination, but a low level of response (low LR) to alcohol was associated only with the risk for AUDs, even when observed in the context of SUDs. The same earlier life characteristics that related to AUDs and to SUDs also related to the combination of these diagnoses in the same person. Finally, in this prospective study subjects with both alcohol and drug use disorders had a more severe course than subjects with either condition alone. CONCLUSIONS: This prospective evaluation of a group at high risk for AUDs confirmed the selective impact of the low LR on the risk for AUDs, the relationship of externalizing characteristics to both AUDs and SUDs, and confirmed the more severe clinical course for both conditions when seen together.